The effectiveness of the formulation of Leucaena leucocephala-based botanical fungicides on blister blight disease (Exobasidium vexans Massee) on tea plant - Dini Jamia Rayati (Jurnal Penelitian Teh dan Kina, 2012)
A study to evaluate the effect of the formulation of L. leucocephala-based botanical fungicide against blister blight disease on tea plant has been conducted in laboratory and in field. In laboratory, the effect of formulation of L. leucocephala-based botanical fungicide was tested against spore germination of E. vexans. The experiment was designed in a randomized complete block (RCB) with ten treatments, replicated three times. The treatments comprised: L. leucocephala-based botanical fungicide in WP and EC formulations, each at concentrations of 0,25%; 0,50%; 1,00%; and 1,50%, standard chemical fungicide at the concentrations of 0,03%, and control. In field, effect of formulation of L. leucocephala-based botanical fungicide was tested against blister blight disease intensity. The trial was conducted at Pasir Sarongge Experimental Garden (1.100 m asl), Cianjur, West Java, designed in a randomized complete block (RCB) with six treatments, replicated fourtimes. The treatments comprised: L. leucocephala-based botanical fungicide in WP formulation at the concentrations of 1,0% and 1,5%, as well as Â in EC formulation at the concentrations of 0,5% and 1,0%, standard chemical fungicide at the dose of 100 g/ha, and control. Results showed that L. leucocephala-based botanical fungicide was effective in inhibiting spore germination of E. vexans in laboratory at concentration of 1,5% for WPÂ  formulation, and at the concentrations of 0,5%; 1,0%; and 1,5% for EC formulation. Their effectiveness were not significantly different to each others, and lower (21%) than standard chemical fungicide treatment (71%). In field, L. leucocephala-based botanical fungicide in WP formulation at concentration of 1,5% (Dose: 4,5 kg/ha) was effective in suppressing blister blight disease intensity after four times of application, and its effectiveness was comparable to standard chemical fungicide treatment, in average reached 31,29%.